Screening Marine Natural Products for New Drug Leads against Trypanosomatids and Malaria - Álvarez-Bardón, María; Pérez-Pertejo, Yolanda; Ordóñez, César; Sepúlveda-Crespo, Daniel; Carballeira, Nestor M.; Tekwani, Babu L.; Murugesan, Sankaranarayanan; Martinez-Valladares, Maria; García-Estrada, Carlos; Reguera, Rosa M.; Balaña-Fouce, Rafael (Marine drugs, 2020)
Neglected Tropical Diseases (NTD) represent a serious threat to humans, especially for those living in poor or developing countries. Almost one-sixth of the world population is at risk of suffering from these diseases and many thousands die because of NTDs, to which we should add the sanitary, labor and social issues that hinder the economic development of these countries. Protozoan-borne diseases are responsible for more than one million deaths every year. Visceral leishmaniasis, Chagas disease or sleeping sickness are among the most lethal NTDs. Despite not being considered an NTD by the World Health Organization (WHO), malaria must be added to this sinister group. Malaria, caused by the apicomplexan parasite Plasmodium falciparum, is responsible for thousands of deaths each year. The treatment of this disease has been losing effectiveness year after year. Many of the medicines currently in use are obsolete due to their gradual loss of efficacy, their intrinsic toxicity and the emergence of drug resistance or a lack of adherence to treatment. Therefore, there is an urgent and global need for new drugs. Despite this, the scant interest shown by most of the stakeholders involved in the pharmaceutical industry makes our present therapeutic arsenal scarce, and until recently, the search for new drugs has not been seriously addressed. The sources of new drugs for these and other pathologies include natural products, synthetic molecules or repurposing drugs. The most frequent sources of natural products are microorganisms, e.g., bacteria, fungi, yeasts, algae and plants, which are able to synthesize many drugs that are currently in use (e.g. antimicrobials, antitumor, immunosuppressants, etc.). The marine environment is another well-established source of bioactive natural products, with recent applications against parasites, bacteria and other pathogens which affect humans and animals. Drug discovery techniques have rapidly advanced since the beginning of the millennium. The combination of novel techniques that include the genetic modification of pathogens, bioimaging and robotics has given rise to the standardization of High-Performance Screening platforms in the discovery of drugs. These advancements have accelerated the discovery of new chemical entities with antiparasitic effects. This review presents critical updates regarding the use of High-Throughput Screening (HTS) in the discovery of drugs for NTDs transmitted by protozoa, including malaria, and its application in the discovery of new drugs of marine origin.